EFFORTS TO IMPROVE CHILDREN’S LANGUAGE SKILLS THROUGH THE WORD GUESSING METHOD WITH PICTURE CARD MEDIA - Henny Puerwanti; I'AH (Jurnal Pendidikan Profesi Guru, 2025)
This research is based on pre-action observation results, which indicate that children's language skills at RA Tarbiyatul Banin are still low, especially in vocabulary recognition and understanding letter or word concepts. The aim of this study is to improve children's language skills through the word-guessing method assisted by picture card media at RA Tarbiyatul Banin, Plosorejo Village, Pucakwangi District, Pati Regency, in the 2019/2020 academic year. This issue arises because children's language skills in word-guessing activities are not optimal due to monotonous teaching methods and a lack of activity variation, causing children to feel bored and uninterested. Consequently, their cognitive abilities remain underdeveloped. The research subjects consist of 26 children from RA Tarbiyatul Banin in the 2019/2020 academic year, including 13 boys and 13 girls. The research was conducted at RA Tarbiyatul Banin, Plosorejo Village, Pucakwangi District, Pati Regency. This study employs a classroom action research (CAR) approach, which consists of four stages: (1) Planning, (2) Implementation, (3) Observation, and (4) Reflection. Data collection techniques include observation and documentation. The research was carried out in three cycles: pre-action, Cycle 1, and Cycle 2. The results indicatean improvement in children's language skills through the word-guessing method. This is evident from the pre-cycle learning outcomes, where no children were able to fully participate. However, after improvements in learning during Cycle 1, the "Developing as Expected" (BSB) scale increased by 1.92%. In Cycle 2, the "Well Developed" (BSB) scale reached 25%. Based on these percentage results, the researcher concludes that the word-guessing game assisted by picture cards can effectively improve children's language skills at RA Tarbiyatul Banin, Plosorejo Village, Pucakwangi District, Pati Regency, in the 2022/2023 academic year.